Ag-NOR staining and satellite association in bone marrow cells from patients with mycosis fungoides - Pedrazzini, Estela Maris (1995)
Silver staining of nucleolus organizing regions (Ag-NORs) of acrocentric chromosomes and the frequency of satellite association (SA) in bone marrow (BM) cells from 7 patients with mycosis fungoides (MF), were studied. BM samples of 7 normal healthy individuals were taken as controls. The mean number of Ag-NORs per metaphase was increased in patients (7.20 +/- 0.25) compared with controls (5.40 +/- 0.16) (p < 0.002), related with the increase of the D group. Moreover, a significant higher percentage of Ag-NOR positive cells in patients (71.7 +/- 3.9) than controls (48.0 +/- 7.8) (p < 0.02), was seen. The analysis of SA revealed a significant increase in the percentage of cells with 1-2 association pairs (ASPs) in patients with respect to their controls (p < 0.05), and a trend to a decrease in the percentage of cells without ASPs. Furthermore, a correlation between the number of Ag-NORs and the mean of ASPs per cell was also found for patients (rk = 0.65; p < 0.05). These results may be associated with a certain degree of immaturity, a high proliferative activity and modifications of the growth rate of BM cells in MF patients.